Nutrition almanac - Dunne, Lavon J. (McGraw-Hill, 2002)
Take a bite out of a bestseller!Trusted by health-conscious people for over 30 years, McGraw-Hill's "Nutrition Almanac" - the oldest healthy eating and supplementation guide around - supplies accurate, up-to-date, and impartial information.That's why over 2.5 million copies have been sold! The new Fifth Edition contains the latest material on the nutrition/disease front: solid information on the latest supplementation, herbs, and vitamins; additional exercise/nutrition benefits and interactions; and much more.This book examines the connections between nutrition and disease; clarifies the role of proteins, carbohydrates, fats, vitamins, and minerals; details the optimal supplementation dosages for individual needs; and presents the latest scientific data on health and eating. This book is invaluable to: physicians; nurses; dieticians; scientists; researchers; physical therapists; physician's assistants; chiropractors; sports trainers; and individuals who want reliable, complete, sensible information on the food they eat, the supplements they take, and the effect these have on their bodies.